2021
DOI: 10.3390/coatings11080901
|View full text |Cite
|
Sign up to set email alerts
|

Ecofriendly Water-Based Solution Processing: Preliminary Studies of Zn-ZrO2 Thin Films for Microelectronics Applications

Abstract: This paper demonstrates the high yield and cost effectiveness of a simple and ecofriendly water-based solution processing, to produce Zinc-doped Zirconia (Zn-ZrO2) composite thin films, onto glass substrates, with excellent optical properties that make them of great interest for optical and microelectronics technologies. The effect of Zn variation (given as 10, 15, 20 at.%) on the crystallization, microstructure, and optical properties of ZrO2 film was examined. The addition of Zn did not restructure the ZrO2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…A similar shift toward shorter wavelengths has been observed in amorphous ZrO 2 doped with Zn, attributed to introducing defect states upon doping. [ 38 ]…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A similar shift toward shorter wavelengths has been observed in amorphous ZrO 2 doped with Zn, attributed to introducing defect states upon doping. [ 38 ]…”
Section: Resultsmentioning
confidence: 99%
“…A similar shift toward shorter wavelengths has been observed in amorphous ZrO 2 doped with Zn, attributed to introducing defect states upon doping. [38] Interestingly, the μ-PL spectrum of the ZrO 2 annealed at 1200 °C is deconvoluted into three Gaussian contributions at 2.16 eV (575 nm), 2.43 eV (511 nm), and 2.81 eV (442 nm). Lin et al reported that V O is the principal contribution to the PL signals at 2.64 eV (470 nm) for m-ZrO 2 .…”
Section: D Zro 2 :Zn Microarchitectures: Optical Propertiesmentioning
confidence: 99%
See 2 more Smart Citations